IMPLEMENTATION OF THE HOPE FAMILY PROGRAM (PKH) IN CIBEUREUM DISTRICT SUKABUMI CITY - Rifani Nurul Agfi; Tuah Nur; Dian Purwanti (DIA: Jurnal Administrasi Publik, 2024)
The title of this research is "Implementation of the Family Hope Program in Cibeureum District, Sukabumi City". This research focuses on how to implement the PKH program in the Cibeureum sub-district, Sukabumi City. This research begins with the discovery of problems which in outline there are still many differences in data on existing systems in DTKS which impede the settlement process. The theory used to measure and find out how successful the PKH program is is the policy implementation theory written by Van Meter and Van Horn (1975). The method used in this research is qualitative by collecting data with documentation, interviews, and observation. In determining the informants in this study using the snowball sampling technique. The results of implementing these policies concluded that the results of this study indicated that the implementation of the PKH program in Cibeureum District, Sukabumi City had not fully gone well, when viewed from an inter-organizational communication perspective, there was still communication between implementers and recipients regarding updating data that had not been implemented. But in terms of human resources it can be said that it is very good and the response is positive, and from the government side it fully supports this program, in terms of the economic, social and political environment it is almost going well but in the political environment there are still those who use it for personal interests and needs.